2013
DOI: 10.1080/10803548.2013.11077017
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic Procedure for the Assembly Line Balancing Problem With Postural Load Smoothness

Abstract: This paper presents a heuristic procedure for assigning assembly tasks to workstations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…X GA [94] (3) MRBCRS [95] (3) X [96] (3) X heuristic [97] (3) RIPGA [98] (4) GA [99] (4) GA [100] (4) MOP [101] (4) heuristic [102] (5) MOP [103] (5) GRASP [104] (5) MIP (5) GRASP [106] (5) MOP [107] (5) MOP [108] (6) X [ Regarding the area of health and safety, Ref. [82] consider the suitability of employees by the psychological demand of workstations using a weighted rigidity measure.…”
Section: Assembly Line Balancing Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…X GA [94] (3) MRBCRS [95] (3) X [96] (3) X heuristic [97] (3) RIPGA [98] (4) GA [99] (4) GA [100] (4) MOP [101] (4) heuristic [102] (5) MOP [103] (5) GRASP [104] (5) MIP (5) GRASP [106] (5) MOP [107] (5) MOP [108] (6) X [ Regarding the area of health and safety, Ref. [82] consider the suitability of employees by the psychological demand of workstations using a weighted rigidity measure.…”
Section: Assembly Line Balancing Problemmentioning
confidence: 99%
“…The ergonomic risk from awkward body posture is assessed according to OWAS in [99] and by RULA in [98,100,101]. A multi-objective function is modeled to minimize the variation of the risk value between stations.…”
Section: Assembly Line Balancing Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors found a way to organise clothing assembly tasks at particular workstations. To do this, they assessed both productivity and ergonomics; RULA was used for the latter [99].…”
Section: Textile Manufacturementioning
confidence: 99%
“…Yuan et al (2019) investigated the reconfigurable assembly line balancing problem with the objective of minimizing the SI. Jaturanonda et al (2013) proposed a heuristic procedure to smooth load among workers. Akyol and Bayhan (2011) proposed a particle swarm optimization to smooth the workload on an assembly line where no buffer is allowed.…”
Section: Introductionmentioning
confidence: 99%